Kajian Peningkatan Hasil dan Kualitas Okra Melalui Perlakuan Ragam media Tanam dan Aplikasi Ecoenzym - Sunawan; Djuhari; Ariani, Putri; Zamarudah, Zuhanid (Universitas Islam Malang, 2025)
Okra plants are not widely known by Indonesians, because it is a type of vegetable plant that does not come from Indonesia, therefore the price is still quite expensive when compared to other vegetables, okra enthusiasts are also still small because many do not understand the nutrition and benefits. To determine the effect of the combination of various planting media compositions and the best concentration of Eco Enzyme on the growth and yield of Okra plants. This study used factorial Group Randomized Design (RAK) with treatment of various compositions of growing media (H) and concentration of eco enzyme (E). The results showed that there was an interaction on the weight of the fruit per 3rd harvest crop and the quality of vitamin C. Separately, the treatment of various compositiozs of planting media had an influence on the weight loss variable.